2017
DOI: 10.15282/jmes.11.2.2017.10.0244
|View full text |Cite
|
Sign up to set email alerts
|

Porous titanium alloy/hydroxyapatite composite using powder compaction route

Abstract: Titanium alloys (Ti6Al4V) and hydroxyapatite (HA) are widely used as implant materials. Ti6Al4V has good mechanical properties and corrosion resistance, whereas HA has excellent biocompatibility but its mechanical properties are weak. The combination of properties between Ti6Al4V and HA is expected to produce a superior material for bio-implants. The aim of this work is to analyse the fabricating porous Ti6Al4V/HA composite through powder compaction with the application of two types of space holders. Sodium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The microporosity itself is essential feature for certain application such as in photocatalysis, or as coating material to preserve the adsorptivity of the surface. In addition, porous structure is required property of HAp-based materials to serve biocompatibility and implantability via the absorption of biological metabolites, cell growth, and providing the diffusion of fluids and nutrients by means of capillarity [ [24] , [25] , [26] ]. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The microporosity itself is essential feature for certain application such as in photocatalysis, or as coating material to preserve the adsorptivity of the surface. In addition, porous structure is required property of HAp-based materials to serve biocompatibility and implantability via the absorption of biological metabolites, cell growth, and providing the diffusion of fluids and nutrients by means of capillarity [ [24] , [25] , [26] ]. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The findings were consistent with the finding of Mara (2015) for biocomposite compressive strength obtained as 167 MPa. The compressive strength of porous biocomposites varied depending on the porosity and pore size distribution (Arifin et al, 2017).…”
Section: A Biomechanical and Physical Properties Of Biocompositesmentioning
confidence: 99%
“…Cetinel et al (2019) reported porous titanium possesses a porous structure with interconnected voids, which can facilitate tissue ingrowth and promote osseointegration. However, high porosity in the structure of prostheses affects the strength and can lead to premature failure after clinical implantation (Arifin et al, 2017). According to the results from the selection analysis in Figure 6, gradient biocomposite has proved to be the most suitable for replacing titanium implants as an alternative biocompatible prosthesis with strength, stiffness and fracture toughness values, which most closely approximate cortical bone set parameters.…”
Section: B Selection Analysis Of Biocomposite Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has made palm stearin more accessible to end users as a cost-effective commercial binder. Furthermore, as a palm stearin binder poses few environmental hazards, it is highly recommended for use in MIM [198].…”
mentioning
confidence: 99%